Articulated trilobite ontogeny: suggestions for a methodological standard. (March 2021) - Hughes, Nigel C.; Adrain, Jonathan M.; Holmes, James D.; Hong, Paul S.; Hopkins, Melanie J.; Hou, Jin-Bo; Minelli, Alessandro; Park, Tae-Yoon S.; Paterson, John R.; Peng, Jin; Webster, Mark; Zhang, Xi-Guang; et al.
Abstract: In order to maximize the utility of future studies of trilobite ontogeny, we propose a set of standard practices that relate to the collection, nomenclature, description, depiction, and interpretation of ontogenetic series inferred from articulated specimens belonging to individual species. In some cases, these suggestions may also apply to ontogenetic studies of other fossilized taxa.